2008
DOI: 10.3844/ajbbsp.2008.425.430
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Properties of the Roots of Clerodendron capitatum

Abstract: Abstract:The aim of this study is to investigate the pharmacological effects of the methanolic extract of Clerodendron capitatum, CC, (family verbenaceae). These investigations were carried out on isolated frog rectus abdominus muscle and rabbit aortic strips and jejunum and non-pregnant rat uterus pretreated with oestradiol. Results showed that CC did not demonstrate any contracting, relaxant or blocking effects on frog rectus abdominus muscle and rat aortic strip preparations. The extract produced a concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Administration of cyproheptadine (0.2 µmol) resulted in 86% suppression of uterine smooth muscle contractions stimulated by M. pruriens (Table 1). This observation is in agreement with the findings of other investigators where cyproheptadine was reported to cause powerful inhibition of serotonin induced contraction [27,28,29]. Thus, the contractile activity of M. pruriens in the present study, may have been derived from its serotonin content and its direct stimulation of 5-HT receptors at a low concentration.…”
Section: Discussionsupporting
confidence: 94%
“…Administration of cyproheptadine (0.2 µmol) resulted in 86% suppression of uterine smooth muscle contractions stimulated by M. pruriens (Table 1). This observation is in agreement with the findings of other investigators where cyproheptadine was reported to cause powerful inhibition of serotonin induced contraction [27,28,29]. Thus, the contractile activity of M. pruriens in the present study, may have been derived from its serotonin content and its direct stimulation of 5-HT receptors at a low concentration.…”
Section: Discussionsupporting
confidence: 94%
“…A genus of flowering plants in the family Lamiaceae is called Clerodendrum [1]. In traditional medicine, the species in the genus is used for a variety of purposes due to its antihypertensive, sedative, analgesic, and anti-inflammatory properties, according to pharmacological research [2,3]. The members of this genus thrive in tropical and warm temperate regions worldwide, with the highest concentration found in tropical Africa and southern Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Herbal effects obsrved in diffirent cases (Abdel Wahab et al, 2008;Alhusseini et al, 2010;Balasubramanyam et al, 2006;Hajati et al, 2011;Khaled and Belbraouet, 2009;Mahfouz et al, 2010;Mansi, 2006;Pulakat et al, 2008;Sulaiman et al, 2009;Zhou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%